The Post-Malabo results framework - African Union Development Agency (2024)
These Comprehensive Africa Agriculture Development Programme (CAADP) Post-Malabo Agenda Technical Working Group (TWG) reports provide the analytical foundations and strategic recommendations to guide Africa’s next decade of agricultural transformation under the Post-Malabo Agenda (2026–2035). Developed collaboratively by the African Union Commission, AUDA-NEPAD, Regional Economic Communities, research institutions, and technical partners, the reports synthesise evidence, lessons, and policy options to inform the design of the Kampala CAADP Declaration and Ten-Year Strategy. Together, they address key priorities including agricultural investment and finance, food security and nutrition, inclusive and sustainable agro-industrialisation, trade and market integration, science, technology and innovation, climate change adaptation and resilience, governance, coordination and delivery mechanisms, and data, monitoring, and mutual accountability.